LIFETIME ESTIMATION FROM ACCELERATED RELIABILITY TESTING USING FINITE ELEMENTS ANALYSIS - Sebastian Marian ZAHARIA; Ionel MARTINESCU (Fiabilitate şi Durabilitate)
The paper is focused at the study of the reliability and of the lifetime of ball bearings,using reliability accelerated testing. The main objectives of this paper are: the estimation of thelifetime and reliability of ball bearings. Taking into account the aspects regarding the statisticalprocessing of experimental data, we determined the main reliability parameters, which in turndetermine the main characteristics regarding the performance and the warranty period of the ballbearings. In this paper, the analysis with finite elements was used to validate and to compare thedata resulted from the accelerated reliability tests of the ball bearings